The uncanny memory of Nazi euthanasia, the Risiera di San Sabba and the foibe - Perra, Emiliano (Incontri. Rivista europea di studi italiani, 2015)
Review of: Susanne Knittel, The Historical Uncanny: Disability, Ethnicity, and the Politics of Holocaust Memory, New York, Fordham University Press, 2015, XII + 350 p., ISBN: 9780823262786, 55.00